WORK PRODUCTIVITY REVIEWED FROM LEADERSHIP, DISCIPLINE, APPRECIATION AND MOTIVATION OF DPKPP EMPLOYEES IN KLATEN REGENCY - Joko Wardoyo; Kartika Hendra Titisari; Istiatin Istiatin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the influence of leadership, discipline, appreciation and motivation on a variable called DPKPP Klaten Regency work productivity. The research that has been done uses an approach called quantitative. The population in this study were all employees at DPKPP Klaten Regency, all of which totaled 75 people. The sampling technique uses saturated samples. The technique for data analysis in this research that has used an analysis called multiple linear regression. The results of a study that has been conducted show that leadership, discipline, appreciation and motivation have a positive and significant impact on a variable called work productivity in DPKPP Klaten Regency. It is hoped that the DPKPP Klaten Regency in the future will continue to maintain and improve the quality of leadership, discipline, appreciation and motivation in employees, so that work productivity will also continue to increase and of course be better than before. Keywords: Work Productivity, Leadership, Discipline, Reward and Motivation